2015
DOI: 10.5005/jp-journals-10001-1245
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications of Thyroid Surgery: A Corroborative Study with an Overview of Evolution of Thyroid Surgery

Abstract: Background:To study the frequency of postoperative complications after thyroid surgery indicated for various benign and malignant lesions and to corroborate the results in relation to the extent of surgery and a clinical overview of evolution of thyroid surgery. Materials and methods:An analytical study was carried out at a tertiary care center over a period of 3 years from January 2011 to December 2013. Data were collected from 80 patients who underwent thyroidectomies for various thyroid diseases at this cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Even though there has been a trend towards performing procedures as an outpatient as permitted by advancements in anesthetic and surgical techniques (Steward, 2014) again, patients are more inclined to perform inpatient thyroidectomy due to significant comorbidity, simultaneous neck, and mediastinal procedures, and social circumstances not conducive to outpatient surgery (Balentine & Sippel, 2016; Sahmkow et al, 2012;S⊘rensen & Klug, 2015). In this study, we found that the rates of complications after total thyroidectomy surgery are relatively high compared to previously reported data from another study (Pandey et al, 2015). We found that patients older than 41 years old and with one or more comorbid conditions were at increased risk for postoperative complications.…”
Section: Discussioncontrasting
confidence: 44%
“…Even though there has been a trend towards performing procedures as an outpatient as permitted by advancements in anesthetic and surgical techniques (Steward, 2014) again, patients are more inclined to perform inpatient thyroidectomy due to significant comorbidity, simultaneous neck, and mediastinal procedures, and social circumstances not conducive to outpatient surgery (Balentine & Sippel, 2016; Sahmkow et al, 2012;S⊘rensen & Klug, 2015). In this study, we found that the rates of complications after total thyroidectomy surgery are relatively high compared to previously reported data from another study (Pandey et al, 2015). We found that patients older than 41 years old and with one or more comorbid conditions were at increased risk for postoperative complications.…”
Section: Discussioncontrasting
confidence: 44%
“…Alqahtani et al found that in Saudi Arabia, females reported more complications than males among all patients who had undergone thyroidectomies [ 10 ]. A 2013 study by Pandey et al found that 70 out of 80 patients were females [ 11 ]. A 2021 study by Alqahtani et al found that 151 of 182 patients were females [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sound knowledge of the thyroid anatomy and surgical nuances of thyroidectomy determine the outcomes and limit the post-operative complications. 4 Ramirez et al stated that post-operative complications are directly related to the expanse of thyroidectomy and have an inverse relation with the surgeon's expertise. 5 Despite the magnitude of the problem in routine clinical practice, the studies investigating the incidences of thyroidectomy complications and their predictive factors in this region of the country are very limited.…”
Section: Introductionmentioning
confidence: 99%